CRESCIMENTO E ACÚMULO DE FÓSFORO EM FEIJÃO-MUNGO CULTIVADO EM CAMBISSOLO ADUBADO COM DIFERENTES FONTES E DOSES DE FÓSFORO - Queiroga, Fabio Martins de; Costa, Samuel Ângelo Diógenes da; Pereira, Francisco Hevilásio Freira; Maracajá, Patrício Borges (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2010)
This study aimed to evaluate the response of mung-bean cultivated in inceptisol fertilized with different sources and levels of phosphorus and its correlation with the extraction of P from the soil using the extractor Mehlich-1. The experiment was conducted in a greenhouse belonging to the Federal Rural University of Semiarid (UFERSA) Mossoro-RN, in the period of 15/09/2000 to 20/10/2000, using a variety of mung-bean 'Green Mungo'. The treatments were consisted of two sources of phosphorus (phosphoric acid and phosphate monopotassium) and five doses of P2O5 (0, 200, 400, 600 and 800 kg ha-1). The experimental design was completely randomized in a factorial 2 x 5 with four replications. The source and P levels provided changes in height and levels of phosphorus in plant and soil and exchangeable potassium in soil. The extractor Mehlich-1 has a greater capacity for recovery of phosphorus from the soil fertilized with phosphoric acid. The higher concentration of K in soil fertilized with KH2PO4, corroborate with the hypothesis that this fertilizer has problems of precipitation and release of exchangeable potassium in contact with the ground.